2017
DOI: 10.5194/bg-2017-391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncertainty of the global oceanic CO<sub>2</sub> uptake induced by wind forcing: quantification and spatial analysis

Abstract: Abstract. The calculation of the air-water CO 2 exchange (FCO 2 ) in the ocean not only depends on the gradient in CO 2 partial pressure at the air-water interface but also on the parameterization of the gas exchange transfer velocity (k) and the choice of wind product. Here, we present regional and global-scale quantifications of the uncertainty in FCO 2 induced by several widely used k-formulations and 4 wind speed data products (CCMP, ERA, NCEP1 and NCEP2). The analysis is 10 performed at a 1° x 1° resoluti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Recently the evaluation of wind speed products has indicated that a 0.09 Pg C yr -1 Roobaert et al, 2018) uncertainty stems from the wind speed uncertainty. We have shown a slightly Manuscript submitted to Global Biogeochemical Cycles larger but still consistent value of 0.14 Pg C yr -1 (Table 2) using a different methodology.…”
Section: 2integrated Air-sea Co 2 Flux Uncertaintiesmentioning
confidence: 99%
“…Recently the evaluation of wind speed products has indicated that a 0.09 Pg C yr -1 Roobaert et al, 2018) uncertainty stems from the wind speed uncertainty. We have shown a slightly Manuscript submitted to Global Biogeochemical Cycles larger but still consistent value of 0.14 Pg C yr -1 (Table 2) using a different methodology.…”
Section: 2integrated Air-sea Co 2 Flux Uncertaintiesmentioning
confidence: 99%
“…The effect of different wind speed products and parameterizations have been detailed in Roobaert et al (2018), including discussion of the rationale for normalizing the wind products and gas transfer-wind speed dependencies. Two different parameterizations are compared here that differ in their assumptions of environmental forcing as detailed in Wanninkhof et al (2009).…”
Section: Sensitivity Of Sea-air Co 2 Fluxes To Different Input Variablesmentioning
confidence: 99%
“…Different gas transfer velocity formulations and wind speed products can impact the global flux estimates with past studies indicating that this is a primary source of uncertainty in global flux estimates (Woolf et al, 2019). The impact of time averaging and the effect of different wind fields has been investigated (Wanninkhof et al, 2002;Roobaert et al, 2018;and Gregor et al, 2019) but conical quadratic wind speed relationships to parameterize gas transfer are used in most flux estimates, including those in RECCAP2 (DeVries et al, 2023) and the GCB (Friedlingstein et al, 2022). A common procedure is to normalized the coefficient in the relationship (Eqn.…”
Section: Sensitivity To the Gas Transfer Velocitymentioning
confidence: 99%
See 1 more Smart Citation